The Killing of Karen Silkwood: The Story Behind the Kerr-McGee Plutonium Case - Sass, Robert (Relations industrielles / Industrial Relations, 2001)
The Killing of Karen Silkwood: The Story Behind the Kerr-McGee Plutonium Case, 2nd edition, by Richard Rashke, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Nuclear accidents & safety; Nuclear industry; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Whistleblowing; Working conditions